Increased manufacturing performance in the light of the theory of constraints: the case of a mattress factory - Silva, André Luiz Emmel (2017)
The Theory of Constraints (TOC) makes possible to identify, control and manage gaps in the best way possible at any productive system by using five steps to do the restrictions management. The goal of this work is to increase the productive process performance with the exclusion of gaps through the application of the Theory of Constraints and the guidelines of the focalization’s five steps in a mattress factory located at Rio Grande do Sul. The research was done with an exploratory objective and descriptive nature to the Theory of Constraints, action research with interventions and also other evaluation techniques, analysis and identification to the process improvement, where they show themselves as supporting tools. The results relate to the identification of gaps, gaps process notion and its elimination. With the TOC 1 (held in the packaging sector and review) the amount of parts per hour increased from 43 to 51 with the step 2, which is equivalent to 18,6%, and after in the step 4 from 51 to 72 parts, a 41% increase by the purchase of an automatic packing machine, also in this TOC was possible a reduction of employees from 5 to 3. With the TOC 2 (held in the assembly sector) the increase of the parts amount was from 59 to 71, about 25%, by the layout and production flow changes, counting with the employees reduction from 17 to 11 in the sector. With the results there was significant production gains, increasing by that this factory unit performance.